2015
DOI: 10.5216/rpt.v43i4.33609
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico Parasitológico E Molecular De Enteroparasitos Entre Crianças Residentes E Funcionários De Uma Institução Beneficente Para Menores No Município De Niterói-Rj, Brasil

Abstract: Os enteroparasitos são causa importante de agravos à saúde humana e podem interferir de forma significativa no desenvolvimento infantil. Embora as formas de transmissão sejam bem documentadas, a desinformação e as precárias condições socioeconômicas de alguns segmentos da população ainda são fatores que contribuem para a manutenção de parasitos no País, viabilizando a transmissão. Este estudo foi realizado entre crianças residentes e funcionários de uma instituição filantrópica religiosa, situada na cidade de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…However, 100% negativity was noted for the presence of Entamoeba histolytica by using the ELISA method to test these same samples. The results presented in this study are similar to those reported by Leite et al (2014) in Niteroi, in which a low index was observed for this protozoan, with only one of the seven samples testing positive for Entamoeba histolytica detected using ELISA.…”
Section: Resultssupporting
confidence: 90%
“…However, 100% negativity was noted for the presence of Entamoeba histolytica by using the ELISA method to test these same samples. The results presented in this study are similar to those reported by Leite et al (2014) in Niteroi, in which a low index was observed for this protozoan, with only one of the seven samples testing positive for Entamoeba histolytica detected using ELISA.…”
Section: Resultssupporting
confidence: 90%
“…As water supply and sewage conditions were similar in the studied areas, it is reasonable to infer the participation of poor hygiene and uncollected garbage as risk factors, as reported previously (Leite et al, 2014;Santos et al, 2014a;Costa et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…A survey carried out in a socio-educational center in Brazil showed that 42.4% of the analyzed individuals, including minors and employees, were positive for enteroparasitosis, being this prevalence much higher than the one identified in our study 18 . In children living in a welfare institution for minors in the city of Niterói, RJ and its employees, 70 and 44% of positive results were obtained for intestinal parasitic diseases, respectively, in children and staff 19 . Therefore, a great difference between the results observed in the present study and those found by other authors was found, investigating populations of children of similar age, considering that the positive patients were…”
Section: This Study Points Out Two Risk Factors Present In the Popula...mentioning
confidence: 97%
“…Regarding the guardians, it was possible to detect 28.5% of positive results, which allowed a lower rate of enteroparasitosis to be observed when compared to the study carried out with employees of a charity, which indicates that 44% of collaborators were positive for enteroparasitosis 18 . It was demonstrated that 38.6% of the positive among the employees of eight daycare centers 19 . Another study showed that the prevalence was 16.7% in the employees analyzed in a daycare center 20 , a lower frequency among employees compared to our study.…”
Section: Children It Should Be Emphasized That the Presence Of Neurol...mentioning
confidence: 99%